Pragmatic Anomalies in Media Texts of “Show “Uralskiye Pelmeni” - Y. A. Yesina (Научный диалог)
The analysis of humorous media texts is carried out from the point of view of presence in them of pragmatic anomalies as a kind of language anomalies. The author assumes that consideration of pragmatic language anomalies of media texts of “Show “Uralskiye Pelmeni” within the framework of the theory of language anomalies allows to trace features of their functioning as means of the organization of entertaining texts. The novelty of the research is determined by the fact that, despite the great interest of linguists in the study of the language game and the wide popularity of the “Show “Uralskiye Pelmeni,” the anomalies on which this media text is built, have not previously been analyzed. The main types of pragmatic anomalies are characterized: pragmatic-semantic and communicative-pragmatic. The following anomalies are attributed to pragmatic-semantic ones: contradiction between pragmatic presuppositions and assertive components of the meaning of a word, phrase or utterance; abnormal actualization of deictic indices; excessive “literalism” of pragmatic presuppositions; abnormal reference. Among the communicative-pragmatic anomalies the following phenomena are analyzed: presence in utterance false discourse implicators; anomalous intentionality of utterances; abnormal reasoning; abnormal operation of speech strategies de dicto / de re. The author comes to the conclusion that the presence of different types of pragmatic anomalies is due to the specifics of media text of humorous TV program “Show “Uralskiye Pelmeni,” assuming the presence of comic.